Paul Bunyan fights the monster plants. - Blassingame, Wyatt; Vestal, Herman B. (Champaign, Ill., Garrard Pub. Co., 1974)
Paul Bunyan and his friend Charlie observe that seeds planted in the fertile soil of the North Woods react in an unusual manner.
Keywords: Bunyan, Paul -- (Legendary character) -- Juvenile literature; Bunyan, Paul -- (Legendary character) -- Legends; Folklore -- United States